2020
DOI: 10.1002/mma.6624
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization for stochastic hybrid coupled controlled systems with Lévy noise

Abstract: In this paper, synchronization for stochastic hybrid-delayed coupled systems with Lévy noise on a network (SHDCLN) is investigated via aperiodically intermittent control. Here time delays, Markovian switching and Lévy noise are considered on a network simultaneously for the first time. After that, by means of Lyapunov method, graph theory, and some techniques of inequality, some sufficient conditions are derived to guarantee the synchronization for SHDCLN. In addition, the designed range of aperiodically inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In comparison to the Brownian motion, the Lévy process has been provided the possibility to describe this discontinuous process. To build more realistic models, many scholars incorporated the Lévy process into a hybrid system (Li and Deng (2017); Lu and Ding (2019); Zhou et al (2020)). Naturally, it is also very important to study the stability of hybrid systems driven by the Lévy process.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the Brownian motion, the Lévy process has been provided the possibility to describe this discontinuous process. To build more realistic models, many scholars incorporated the Lévy process into a hybrid system (Li and Deng (2017); Lu and Ding (2019); Zhou et al (2020)). Naturally, it is also very important to study the stability of hybrid systems driven by the Lévy process.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in [27][28][29][30][31], the models considered have been largely restricted to deterministic ordinary differential equations. In fact, multi-weighted complex networks are inevitably affected by various types of environmental noise [33][34][35][36][37]. However, it should be noted that there are few papers about partial topology identification [32] of stochastic multi-weighted complex networks.…”
Section: Introductionmentioning
confidence: 99%
“…Synchronisation, as one of the typical collective behaviours of complex dynamical networks, has stirred up great research interest over the past few decades and fruitful results have been reported (see, for example [1–10] and references therein). It is worth noting that the above literature mainly considers first‐order complex dynamical networks.…”
Section: Introductionmentioning
confidence: 99%